The warm forming of aluminium/magnesium alloy sheet - Shehata, Farouk (Cranfield University, 1979)
The desire to reduce the overall motor vehicle weight, and so use less fuel, means that aluminium alloys are now being considered for car bodies. Unfortunately, increase in strength generally leads to a decrease in ductility, because of the alloying additions. Warm forming however , of the Al/Mg series of alloys restores and enhances ductility to a remarkable degree. Cont/d